Service Quality Evaluation: The Empathy Gap in Ngampelsari Village Administration: Evaluasi Kualitas Layanan: Kesenjangan Empati dalam Administrasi Desa Ngampelsari - Anggraeni, Dian Adiana; Mursyidah, Lailu (Indonesian Journal of Public Policy Review, 2025)
General Background: High-quality public services, especially in population administration at the village level, are central to the success of local governance. Specific Background: Despite their critical role, population administration services often face challenges related to resource limitations and procedural compliance, making continuous quality evaluation necessary. Knowledge Gap: Prior studies show inconsistent service quality, and there is a need for a specific, comprehensive assessment of service delivery at the Ngampelsari Village Government. Aims: This research aims to describe and analyze the quality of population administration services using the five Servqual dimensions, and to identify the primary supporting and inhibiting factors. Results: Findings indicate that four dimensions—Tangibles, Reliability, Responsiveness, and Assurance—are optimal. However, the Empathy dimension is less than optimal, primarily due to a lack of awareness among service officers. Inhibiting factors include limited human resources and inadequate network infrastructure. Novelty: This study offers a Servqual-based diagnostic tool applied specifically to a village-level administrative service, highlighting the critical role of human factor awareness over mere procedural compliance. Implications: The results urge the village government to prioritize targeted soft skills training to enhance officer empathy and mitigate the human resource gap. Highlights Four out of five Servqual dimensions (Tangibles, Reliability, Responsiveness, and Assurance) are considered optimal. The Empathy dimension is the primary quality gap due to low awareness among service officers. Service barriers include limited human resources and inadequate network infrastructure. Keywords: Service Quality, Empathy, Population Administration, Servqual, Ngampelsari Village